Gottron's acrogeria and peliosis hepatis - Gloria Cobo Ramírez; Monica Lopez Rodriguez; Andres Gonzalez Garcia; Marta Rosas Cancio-Suarez; Luis Adrian Viteri; Luis Manzano Espinosa (Global Journal of Rare Diseases - Peertechz Publications, 2019)
We report the case of a 62-year-old woman with Gottron's acrogeria and peliosis hepatis. Gottron's acrogeria is a rare congenital disease characterized by atrophic acral skin with mottled hyperpigmentation and an aged appearance. It is mostly caused by a mutation in COL3A1 gene that leads to defective production of type III collagen.